Fine Mapping of Leaf Trichome Density Revealed a 747-kb Region on Chromosome 1 in Cold-Hardy Hybrid Wine Grape Populations - Yin, Lu; Karn, Avinash; Cadle-Davidson, Lance; Zou, Cheng; Underhill, Anna; Atkins, Paul; Treiber, Erin; Voytas, Daniel; Clark, Matthew (Frontiers in Plant Science, 2021)
Segregation for leaf trichome density was observed in a cold-hardy hybrid grape population GE1025 (N=~125, MN1264 × MN1246) which was previously used to detect a QTL underlying foliar phylloxera resistance on chromosome 14. Our hypothesis was that high trichome density was associated with resistance to phylloxera. Existing literature found trichome density QTL on chromosomes 1 and 15 using a hybrid grape population of ‘Horizon’ × Illinois 547-1 and suggested a few candidate genes. To validate the reported QTL and our hypothesis, interval mapping was conducted in GE1025 with previous GBS SNP genotype data and phenotypic scores collected using a 0-6 trichome density scale at several leaf positions. Evaluations were done on replicated forced dormant cuttings in two years and on field-grown leaves in one year. There was no strong relationship between trichome density and phylloxera resistance except for a Pearson’s correlation (r) of about -0.2 between a few trichome density traits and phylloxera severity traits at 2 and 3 weeks after infestation. Two genetic regions were repeatedly detected for multiple trichome density traits: from 10 to 20.7 Mbp (~10 Mbp) on chromosome 1 for ribbon and simple density traits and from 2.4 to 8.9 Mbp on chromosome 10 for ribbon density traits, explaining 12.1-48.2% and 12.6-27.5% of phenotypic variation, respectively. to fine map, we genotyped a larger population, GE1783 (N=~1023, MN1264 × MN1246), with conserved rhAmpSeq haplotype markers across multiple Vitis species and phenotyped 233 selected potential recombinants. Evaluations were conducted on field grown leaves in a single year. The QTL for ribbon trichome density on adaxial vein and adaxial leaf and simple density on abaxial vein were fine mapped to 12.63 - 13.38 Mbp (747 kb) on chromosome 1. We found insertion/deletion variations of MN1264 and MN1246 in one candidate pseudogene in this region and three other surrounding candidate genes proposed previously. Even though no strong relationship between foliar phylloxera resistance and trichome density was found, this study validated and fine mapped a major QTL for trichome density using a cold-hardy hybrid grape population and shed light on a few candidate genes which has implications for different breeding programs.